Satisfaction with the Service of General Practitioners - Leonavičius, Vylius; Plieskis, Mindaugas; Petrauskienė, Jadvyga (Sociologija. Mintis ir veiksmas, 2003)
The paper discusses the satisfaction with the service of general practitioners (GP) in the primary health care of Kaunas city. The performance of instruction of GP without any questions is the crucial criteria of different biomedical and biopsychosocial pattern of health. Most part of the patients strictly follow the requirements of GP and they are satisfied with service of GP. They interact with GP on the ground of the biomedical pattern of health. On the other hand, some patients didn’t follow the requirements of GP and they are not satisfied with service. We concluded that dissatisfied patients ground their interaction with GP on the biopsychosocial pattern of health. Both patterns reflect to the different types of society. Biomedical pattern characterizes society with strong institutional constraints and biopsychosocial model of interaction is a feature individualistic society.
Keywords: healt care; satisfaction with service; general practicioner–patient relationship